The Kiai’s Cultural Strategy in Shaping the Religious Culture of the Community of Temboro Magetan Village, East Java - Zainal Arifin; Maragustam Maragustam; Muqowim Muqowim; Hafidh 'Aziz (UIN Sultan Aji Muhammad Idris Samarinda, 2021)
Religious culture in the village of Temboro, which made it is known as